Implementation of interface damage model with friction to concrete-FRP shear connector (Fracture and Structural Integrity, 2025)
The study investigates the application of fibre-reinforced polymer (FRP) composites in constructions of bridges. It highlights the main advantages of using FRP as a building material and points out its suitability for various structural applications. A numerical analysis was performed on different shape modifications of a jigsaw-puzzle type continuous shear connector. For the interface between concrete and FRP, a bilinear cohesive zone model with friction within a variationally based formulation of interface damage has been chosen and tested. This model captures the load displacement relation accounting for a softening region and offering a continuous response of key variables of stress and damage. Findings illustrate reliability of the cohesive bilinear model as a tool for predicting failure and show a promise for applying it in material design, or in design of FRP composite structures, their members and specifications of their construction details.
Keywords: Cohesive damage model; energy formulation; concrete; FRP composite; shear connector; interface